ASSESSING CHANGES IN LAND RENT COSTS AND THEIR IMPACT ON THE FINANCIAL PERFORMANCES OF AGRICULTURAL HOLDINGS IN BULGARIA - D. Kirechev (Trakia Journal of Sciences)
The report analyses change in the cost of land rent on farms. It analyses the impact of rent expenditure on farm financial performance by farm type and regionally. It is argued that rising rent costs have a negative impact on the financial performance of farms and put pressure on their efficiency. This is more pronounced in areas specializing in intensive crop production, where larger agricultural areas are rented. The external factor costs exceed the farming overheads. There is a need for farmers to adopt a more pragmatic policy when renting agricultural land.